PENGARUH PENYULUHAN MAKANAN BERGIZI DENGAN METODE ULAR TANGGA TERHADAP PENINGKATAN PENGETAHUAN ANAK-ANAK - Nurul Hidayah; M. Thonthowi Jauhari; M. Zulfikar Al fariki (Poltekkes Kemenkes Mataram, 2021)
Background : Health issues in Indonesia are still on the top topic. One of them is malnutrition and obesity which cause Indonesia encounters “double burden of malnutrition”. Sharing knowledge to children is a good starting point to fix the issue. This can increase children’s knowledge and brings Indonesia to escalate the quality of human resources in the future. Objective : The purpose of this research is to know the effectivity of socialization hold by ladder game method to the elevation of children’s knowledge into nutritious foods. Method : This has been done by three main steps; pre-test session, intervention, and post-test session. During pre-test and post-test, students were given several questions then the answers were analyzed using SPSS. Results : The results were analyzed statistically to highlight the description results which depicted that there is an influence of ladder game method during socialization to the increase of children’s knowledge. After giving a post-test, it showed a better result compared to pre-test. During pretest mean was 11.9 while at the post-test it reached approximately 15. Conclusion : It can be said that after the intervention by the ladder game method, the children’s insight is much more increasing even though it had no significancy